2022
DOI: 10.1111/ijpo.12980
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term complications and post‐acute sequelae in hospitalized paediatric patients with COVID‐19 and obesity: A multicenter cohort study

Abstract: Summary Background Obesity increases the severity of coronavirus disease 2019 illness in adults. The role of obesity in short‐term complications and post‐acute sequelae in children is not well defined. Objective To evaluate the relationship between obesity and short‐term complications and post‐acute sequelae of SARS‐CoV‐2 infection in hospitalized paediatric patients. Methods An observational study was conducted in three tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…These include older age, increased body mass index, and allergic diseases 22,24,45,53 . In particular, links between excessive weight and obesity and severe short‐term outcomes and postacute sequelae have been recognized 22,36,54 . In keeping with these reports, in our study group, we noticed pulmonary impairment in teenagers with obesity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These include older age, increased body mass index, and allergic diseases 22,24,45,53 . In particular, links between excessive weight and obesity and severe short‐term outcomes and postacute sequelae have been recognized 22,36,54 . In keeping with these reports, in our study group, we noticed pulmonary impairment in teenagers with obesity.…”
Section: Discussionsupporting
confidence: 87%
“…22,24,45,53 In particular, links between excessive weight and obesity and severe short-term outcomes and postacute sequelae have been recognized. 22,36,54 In keeping with these reports, in our study group, we noticed pulmonary impairment in teenagers with obesity. However, our results cannot be directly compared to those presented above as we included only patients with COVID-19 pneumonia (irrespective of prolonged symptoms).…”
Section: While Increasing Number Of Studies Assessing Children After ...supporting
confidence: 91%
“…Available findings and knowledge regarding LC sequelae are limited. Evidence in children and adolescents has indicated that obesity is associated with the severity of LC sequelae (235). LC-related symptoms were associated with a change in body weight that was independent of the patient's initial COVID-19 status (236).…”
Section: Obesity and Covid-19mentioning
confidence: 99%